Smart Egg Incubator Based on IoT and AI Technology for Modern Poultry Farming - Wahyuni, Refni; Irawan, Yuda; Febriani, Anita; Nurhadi, Nurhadi; Tri Saputra, Haris; Andrianto, Richi (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2024)
The productivity of egg hatching in the poultry industry is often hindered by conventional methods, resulting in low hatch rates and slow production. This study introduces the UHTP (Universitas Hang Tuah Pekanbaru) Smart Egg Incubator, which incorporates Internet of Things (IoT) and Artificial Intelligence (AI) technologies, specifically the Mamdani Fuzzy Logic Algorithm, to enhance egg hatchability. The incubator features a 100-egg capacity, automatic temperature and humidity control, cooling systems, and real-time monitoring via mobile devices. It also includes a camera for movement detection, capturing images of hatching eggs, and sending notifications to users. The automatic egg-turning mechanism ensures even temperature distribution. Experimental results show that the incubator maintains optimal temperatures between 37.7°C and 38.8°C, with successful hatching observed on the 19th day. The fuzzy logic AI system effectively manages environmental changes, ensuring a stable hatching process by dynamically adjusting the conditions within the incubator. The user-friendly interface and remote monitoring capabilities provide convenience and efficiency for poultry farmers. This innovative design significantly improves hatch rates and supports the economic productivity of chicken farming, offering practical solutions for modern poultry farming. The integration of this AI technology can lead to higher profitability and sustainability in poultry farming, addressing common challenges such as inconsistent environmental conditions and labor-intensive processes, thus contributing to the advancement of agricultural practices